Mathematical models and simulations of different scenarios of COVID-19 in Brazil - Lima, Marina (2023)
In this paper, we develop successive mathematical models for describing the first and second waves of COVID-19 in Brazil, including the origi[1]nal strain, the two variants with the highest circulation (Gamma and Delta variants) and population vaccination. We started with a a simple initial model and using mathematical modelling techniques and the Heaviside step function, we improved it according to the necessities of describing the disease’s behaviour, both considering the new variants or vaccination. In all cases, we performed computer simulations and compared the obtained curve with real data from the active cases, which reinforced the model’s efficiency in describing the behaviour of the pandemic and highlighted the importance of population vaccination in describing the dynam[1]ics of the infections and reducing cases.